2008
DOI: 10.1093/jee/101.5.1540
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Granulovirus (PoGV) and Bacillus thuringiensis subsp. kurstaki for Control of the Potato Tuberworm (Lepidoptera: Gelechiidae) in Stored Tubers

Abstract: Liquid suspensions and dry formulations of a granulovirus (family Baculoviridae, genus Granulovirus, PoGV) derived from infected larvae and the bacterium Bacillus thuringiensis subsp. kurstaki (Berliner) (Btk) were evaluated for control of the potato tuberworm, Phthorimaea operculella (Zeller) (Lepidoptera: Gelechiidae), in stored tubers. Laboratory bioassays at 25 degrees C showed that both PoGV and a wettable powder (WP) formulation of Btk incorporated with carriers (water, talc, sand, diatomaceous earth, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 0 publications
2
18
0
Order By: Relevance
“…At the highest rate (5×10 8 ) of both aqueous suspension and virus formulation, no feeding damage of first instars on the tubers was observed (data not shown), and most likely due to overdose. Arthurs et al (2008) also verified 100% potato tuberworm larval mortality with concentrations as low as 5.75×10 8 OBs/kg. Talc was tested as a dust carrier for virus OBs, but we observed that the talc itself strongly affected larval mortality of potato tuberworm due to its fast desiccation effect against newly hatched larvae, as previously described elsewhere (Alcázar et al 1992b, Arthurs et al 2008.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…At the highest rate (5×10 8 ) of both aqueous suspension and virus formulation, no feeding damage of first instars on the tubers was observed (data not shown), and most likely due to overdose. Arthurs et al (2008) also verified 100% potato tuberworm larval mortality with concentrations as low as 5.75×10 8 OBs/kg. Talc was tested as a dust carrier for virus OBs, but we observed that the talc itself strongly affected larval mortality of potato tuberworm due to its fast desiccation effect against newly hatched larvae, as previously described elsewhere (Alcázar et al 1992b, Arthurs et al 2008.…”
Section: Discussionmentioning
confidence: 68%
“…Arthurs et al (2008) also verified 100% potato tuberworm larval mortality with concentrations as low as 5.75×10 8 OBs/kg. Talc was tested as a dust carrier for virus OBs, but we observed that the talc itself strongly affected larval mortality of potato tuberworm due to its fast desiccation effect against newly hatched larvae, as previously described elsewhere (Alcázar et al 1992b, Arthurs et al 2008. Some dry powder carriers have been used as an alternative to synthetic insecticides and are thought to act by imposing mechanical disruption (e.g., mouth parts injuries on chewing insects such as beetles and caterpillars) and physiological stress by absorbing wax from the insect cuticle resulting in water loss (Ebeling 1971, Korunic 1998).…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…However, microbial control of P. operculella is not yet developed for massive commercial use although some authors have indicated the potential use of those pathogens in the future (Lacey and Arthurs 2005;Arthurs et al 2008). In fact, some small scale tuberworm control by microbes has been already used successfully (Kroschel et al 1996a, b;Sporleder et al 2001Sporleder et al , 2005Sporleder 2003).…”
Section: Parasitoids and Predatorsmentioning
confidence: 99%